2012
DOI: 10.1007/s10903-012-9578-6
|View full text |Cite
|
Sign up to set email alerts
|

The Health Profile and Chronic Diseases Comorbidities of US-Bound Iraqi Refugees Screened by the International Organization for Migration in Jordan: 2007–2009

Abstract: More than 63,000 Iraqi refugees were resettled in the United States from 1994 to 2010. We analyzed data for all US-bound Iraqi refugees screened in International Organization for Migration clinics in Jordan during June 2007-September 2009 (n = 18,990), to describe their health profile before arrival in the United States. Of 14,077 US-bound Iraqi refugees ≥ 15 years of age, one had active TB, 251 had latent TB infection, and 14 had syphilis. No HIV infections were reported. Chronic diseases comorbidities accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 18 publications
4
65
1
Order By: Relevance
“…This may also affect the health behaviors of deportees. Muñoz et al (2013) found that HIV-positive deportee patients were significantly less likely to be adherent to their antiretroviral medication (AOR: 0.35; 95% CI: 0.12–0.96), compared to non-deported HIV-positive patients [46]. Access to health services and HIV testing is a critical issue for reducing HIV transmission and preventing disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…This may also affect the health behaviors of deportees. Muñoz et al (2013) found that HIV-positive deportee patients were significantly less likely to be adherent to their antiretroviral medication (AOR: 0.35; 95% CI: 0.12–0.96), compared to non-deported HIV-positive patients [46]. Access to health services and HIV testing is a critical issue for reducing HIV transmission and preventing disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the highest diabetes prevalence countries are in the Middle East, and one recent cross-sectional survey in Iraq found a crude rate of diabetes among adults of 19.7 % [10]. Other refugeefocused studies also found diabetes to be a major cause of morbidity in Iraqis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…14 -16 Refugee children arrive in the United States with variable nutritional status based on their preresettlement experiences. 9,12,17,18 Although several studies have reported an increase in the prevalence of obesity and obesity-related diseases among adult refugees and an increase in their BMI trajectories after US resettlement, the data among child refugees is limited. 19,20 Two small studies demonstrated a trend toward increasing obesity prevalence among refugee children.…”
Section: What This Study Addsmentioning
confidence: 99%